2020
DOI: 10.5688/ajpe7693
|View full text |Cite
|
Sign up to set email alerts
|

Using a Mixed Methods Approach to Explore Perceptions of Early Learners in Classroom-Based Interprofessional Education Experiences

Abstract: Objective. To explore attitudes and learning outcomes among early-level health professions students who completed foundational interprofessional education (IPE) courses. Methods. This study used a mixed methods approach to examine assessment and evaluation data from two student cohorts enrolled in two one-credit, semester-long interprofessional courses taught in fall and spring 2017. Attitudinal changes following the fall course were measured and compared in a retrospective pretest-posttest manner across stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
1
4
1
Order By: Relevance
“…[12][13][14][15] The results of our study are largely in agreement with previous studies where the SPICE-R2 tool was used, where among the three subscales, the change in student attitudes toward interprofessional roles and responsibilities was the greatest. 14,15 Despite other studies demonstrating a significant change found only in the 'Roles/Responsibilities for Collaborative Practice' and 'Patient Outcomes from Collaborative Practice' subscales, 16 in our study, a significant change in students' attitudes towards interprofessional teamwork was observed in the third-year undergraduate pharmacy, final year pharmacy, first year and third year PharmD students. A statistically significant difference in all three subscales is an important outcome since it indicates a shift in three foundational IPE constructs.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…[12][13][14][15] The results of our study are largely in agreement with previous studies where the SPICE-R2 tool was used, where among the three subscales, the change in student attitudes toward interprofessional roles and responsibilities was the greatest. 14,15 Despite other studies demonstrating a significant change found only in the 'Roles/Responsibilities for Collaborative Practice' and 'Patient Outcomes from Collaborative Practice' subscales, 16 in our study, a significant change in students' attitudes towards interprofessional teamwork was observed in the third-year undergraduate pharmacy, final year pharmacy, first year and third year PharmD students. A statistically significant difference in all three subscales is an important outcome since it indicates a shift in three foundational IPE constructs.…”
Section: Discussionsupporting
confidence: 90%
“…Early familiarity and involvement in IPE experiences may help pharmacy students to modify the consideration of their own role, from an individual professional who works in a community setting to a vital member of a wider network of care. 14 Participation in IPE activities and workshops may be beneficial in achieving this goal. 17 Regarding the PharmD groups, there was an increase in mean scores in the second and third year students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, academic level should be considered when evaluating introductory IPE experiences offered to students at different academic levels. For example, several studies have reported differences in student attitudes between health science disciplines when students are at different academic levels within each discipline (Lockeman et al, 2017;Matulewicz et al, 2020;McGregor et al, 2018;Muzyk et al, 2020). Potentially, differences in academic level may confound reported differences between health professions.…”
Section: Discussionmentioning
confidence: 99%
“…Early learners at different academic levels are likely to have very different backgrounds and experiences, and these differences may affect students' responses to an introductory IPE experience. A few studies have reported the impact of an introductory IPE experience on students at both the undergraduate and graduate levels using the Student Perceptions of Interprofessional Clinical Education-Revised instrument, version 2 (SPICE-R2) (Lockeman et al, 2017;Matulewicz et al, 2020;Mc-Gregor et al, 2018;Muzyk et al, 2020). Although these studies demonstrated various improvements in students' attitudes about IPE at both academic levels, they did not examine the effect of academic level on students' attitudes before participating in the IPE experience or the magnitude of attitude change following the IPE experience.…”
Section: Implications For Interprofessional Practicementioning
confidence: 99%